Sejarah Masuknya Islam dan Pendidikan Islam Masa Kerajaan Banten Periode Pra Kemerdekaan - Muslimah muslimah (Jurnal Studi Agama dan Masyarakat, 2017)
The coming of islamic scholars as Islamic spreader in Banten must deal with the condition of the people who had embraced Hinduism. The people were already familiar with the superstitions of heresy and khurafat. The cause of this condition were stupidity, clumsiness and Dutch colonialism. This literature review will ease the observers of history and Islamic education, because this literature review discusses specifically and systematically about the history of the entry of Islam and Islamic education in the Sultanate of Banten in the period of 1552-1935 years. The findings of this study explain that the entry of Islam in the Sultanate of Banten was done peacefully by Sharif Hidayatullah (Sunan Gunung Jati) together with his son, Maulana Hasanudin, who then became the first sultan of Sultanate of Banten, continued by Maulana Yusuf and the next sultans; What Islamic scholars did in the Sultanate of Banten such as spreading the teachings of Islam as well as balancing life and religion, eradicating stupidity and encouraging jihad against the invaders; At first, Islamic educational institutions in Banten were conducted in homes and mosques individually and then got developed into madrasah.